Delivery of Human iPSC-Derived RPE Cells in Healthy Minipig Retina Results in Interaction Between Photoreceptors and Transplanted Cells - Macečková Brymová, Anna; Rodriguez-Jimenez, Francisco Javier; Konrad, Annika; Nemesh, Yaroslav; Thottappali, Muhammed Arshad; Artero-Castro, Ana; Nyshchuk, Ruslan; Kolesnikova, Anastasiia; Müller, Brigitte; Studenovska, Hana; Juhasova, Jana; Juhas, Stefan; et al. (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2025)
In late stages of inherited and acquired retinal diseases such as Stargardt disease (STGD) or dry age-related macular degeneration (AMD), loss of retinal pigment epithelia (RPE) cells and subsequently photoreceptors in the macular area result in a dramatic decline of central visual function. Repopulating this area with functional RPE cells may prevent or decline the progression of photoreceptor loss. In the present study, the viability, survival, and integration of human induced pluripotent stem cell (hiPSC)-derived RPE cells (hiPSC-RPE) is assessed generated using clinical-grade protocol and cultured on a clinically relevant scaffold (poly-L-lactide-co-D, L-lactide, PDLLA) after subretinal implantation in immunosuppressed minipigs for up to 6 weeks. It is shown that transplanted hiPSC-RPE cells maintain the RPE cell features such as cell polarity, hexagonal shape, and cell-cell contacts, and interact closely with photoreceptor outer segments without signs of gliosis or neuroinflammation throughout the entire period of examination. In addition, an efficient immunosuppressing strategy with a continuous supply of tacrolimus is applied. Continuous verification and improvement of existing protocols are crucial for its translation to the clinic. The results support the use of hiPSC-RPE on PDLLA scaffold as a cell replacement therapeutic approach for RPE degenerative diseases.
Keywords: Animals; Swine, Miniature; retinal degeneration; age‐related macular degeneration; Induced Pluripotent Stem Cells; Retina; lidé; miniaturní prasata; indukované pluripotentní kmenové buňky; Photoreceptor Cells; prasata; cell therapy; Macular Degeneration; Human induced pluripotent stem cells; minipigs; retinální pigmentový epitel; Swine; makulární degenerace; Retinal Pigment Epithelium; retina; zvířata; fotoreceptory; retinal pigment epithelium; Humans